Analysis of Maccera Manurung Values and Their Implications in Counseling Guidance - Zulfikri, Zulfikri; Aryani, Farida; Latif, Suciani (Universitas Negeri Makassar, 2025)
Abstract. The focus of the problem in this research is how; 1) the description of maccera manurung cultural values. 2) what are the implications of Maccera Manurung's cultural values in guidance and counseling services. The purpose of this study is to find out; 1) the description of maccera manurung cultural values. 2) the implications of Maccera Manurung cultural values in guidance and counseling services. Data collection techniques include in-depth interviews, participant observation, and documentation. The data analysis in this study is descriptive, qualitative data analysis. The subjects of this research are traditional figures, students who have implemented Maccera Manurung culture and Counseling Guidance Teacher. The results of this study show a general description of Maccera Manurung culture in the Kaluppini community and the main values in the Maccera Manurung procession that are related to the value of guidance and counseling. these values are described in the maccera manurung culture procession, including: ma’balla (respect for others, empathy, respect for God, cooperation) massajo (responsibility, trustworthiness, courage, honesty, discipline, love for the motherland) kasiturutan (togetherness, regularity, discipline, tolerance, manners). The implications of Maccera Manurung cultural values in the guidance and counseling services in this study were identified in the form of basic services in the field of personal and social guidanceKeywords: Maccera Manurung Cultural Values, guidance and counseling